The Role of Local Government in Supporting Ownership Transformation at Enterprises in Poland After 1990 - Sławomir Kamosiński (European Scientific Journal, ESJ, 2017)
In the history of local government in Poland after the WWII two periods are generally indicated. The first one refers to the years 1950-1989. During that long time interval in Poland local government was dissolved and replaced with national councils, modeled on the Soviet Union solutions. The second period started in 1989 and has lasted up to present day. It is related to restoration of democracy in Poland and also of the local government. Dissolution of the local government in Poland took place on 20th March 1950. On that day the Polish Seym adopted a resolution on territorial units of uniform public authority. Basing on the resolution the system of national councils was constructed, following the Soviet model. National councils did not have attributes allowing to recognize them as local government units. They were deprived of legal personality, own property or budget. Therefore, the role of institution providing for social needs at local level was taken over by enterprises. Such situation deformed life of local community. The concept of local homeland was excluded from use. Transformation of political and economic systems that began in Poland in 1989, and related to it reconstruction of local government, (on the basis of Act of 8th March 1990), enabled restoration of the local government after nearly fifty years of nonexistence. From the moment of reconstruction, the local government took over the responsibility for fulfilling social needs. At the same time enterprises, undergoing the process of restructuring and ownership transformations, as part of the reduction of so-called nonproductive assets, gave to the local governments, often for free, parts of assets that were connected with social activities of plants, for instance: apartments belonging to the enterprise and technical and municipal buildings (water and waste water facilities, water treatment plants and local roads). This paper, basing on selected cases, shows what tasks were carried out by enterprises that replaced local government (first part of the paper), and describes the scale of problem, referred to as enterprises "abandoning" the role meant for the local government after 1990.